Infeksi Kecacingan Pasca Pengobatan Pada Anak Sekolah Dasar di Kabupaten Tebo - Ni Putu Aryadnyani (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2021)
Helminthiasis is an endemic and chronic disease that can cause malnutrition, stunted growth, intellectual retardation, and decreased cognitive abilities. In Indonesia, efforts to eradicate helminthiasis have been carried out through mass drug administration. This study aims to identify helminth infections after treatment with albendazole 400 mg in school children in Tebo district, Jambi province. The design of this study was an observational descriptive study by examining the feces of children who had been given treatment. Based on the results of the examination, it was found that worm infections were 16.7%, with details of 6.7% positive for Ascaris lumbricoides and 10% positive for Trichuris trichiura.